Empirical Validation of the NU-ness Learning Evaluation Instrument to Enhance Educational Quality in Ma’arif Institutions - Subarkah, Imam; Mariana; Fatimah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2025)
Evaluating learning programs within educational institutions is a critical step toward enhancing the quality of education. This study aims to assess the feasibility of a newly developed learning evaluation instrument. The research employed a Research and Development (R&D) methodology following the Borg and Gall model. The instrument underwent expert validation through a Focus Group Discussion (FGD) involving five experts. Practicality was evaluated through field trials, while implementation testing was conducted with administrators of the Ma’arif Educational Institution (LP Ma’arif), school principals, NU-ness subject teachers, and students. Data analysis utilized both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), conducted using LISREL 8.50 for Windows. The findings reveal: (1) the developed instrument demonstrates strong validity and reliability for assessing learning programs; and (2) the field implementation, conducted by institutional leaders and staff, produced an average score (X) of 22. Based on classification criteria (X equal to or greater than 20), this outcome is categorized as “very good.” This instrument can be effectively used to support learning evaluations and improve the overall educational quality in Ma’arif institutions.